Housing, land, and property rights in post-conflict United Nations and other peace operations : a comparative survey and proposal for reform - Leckie, Scott (Cambridge University Press, 2009)
"For more than sixty years, the blue helmets of United Nations Peacekeeping missions around the world have come to symbolize both the promise and the fragility of the UN. Beset with unresolved conflicts and underfunding, and invariably burdened with sentiments of overexpectation, more times than not UN missions to keep the peace have made a difference. In recent years, frequent allegations of corruption, fraud, and abuse have tarnished the image of the UN as not only overly ineffectual, but as something to be skeptical of, rather than the obvious place to turn for help in resolving contentious challenges that affect many nations." "While the ups and downs of UN operations have been analyzed and critiqued, one policy sphere has largely been ignored: the track record of the UN following conflict in the area of housing, land, and property rights. This volume seeks to fill this void by examining the UN's experience in grappling with the immense and inevitable housing, land, and property rights crises that emerge in all countries during and after conflict."--Jacket.